PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING BERBANTUAN MEDIA BAPER TERHADAP MINAT BELAJAR SISWA KELAS V - Herdi Novianto; Anni Malihatul Hawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low interest in learning Indonesian among elementary school students is often attributed to a lack of variety in teaching models and the use of non-interactive media. This situation results in limited active engagement and poor concentration among students during classroom instruction. This study aims to analyze the impact of the Game-Based Learning (GBL) model, supported by BAPER (Baca, Pelajari, Raih Prestasi-Read, Learn, Achieve) media, on the Indonesian language learning interest of fifth-grade elementary students. The study contributes an innovative, game-based interactive learning media alternative designed to boost student engagement at the elementary level. A quantitative approach utilizing a quasi-experimental design (specifically, a non-equivalent control group design) was employed at SD Negeri Suruh 01, involving a sample of 50 fifth-grade students (divided into a control group of 25 and an experimental group of 25). Data were gathered via learning interest questionnaires and observation sheets, then analyzed using the Independent Sample t-Test. The results revealed a significant difference in learning interest between the experimental and control groups tcalculated = 7.447 > ttable = 2.011; p = 0.000 < 0.05. The mean learning interest score for the experimental group (86.50) was significantly higher than that of the control group (78.50). The implementation of the GBL model supported by BAPER media proved effective in enhancing indicators such as feelings of enjoyment, interest, attention, and active student engagement. Consequently, the GBL model supported by BAPER media is concluded to have a positive and significant impact, making it a viable innovative learning alternative for increasing students' interest in learning Indonesian. Keywords: Game Based Learning, BAPER media, learning interest, Indonesian language, elementary school.